Myo‐inositol alters the effects of glucose, leptin and insulin on placental palmitic acid and oleic acid metabolism - Watkins, Oliver C.; Pillai, Reshma Appukuttan; Selvam, Preben; Yong, Hannah E.J.; Cracknell‐Hazra, Victoria K.B.; Sharma, Neha; Cazenave‐Gassiot, Amaury; Bendt, Anne K.; Godfrey, Keith M.; Lewis, Rohan M.; Wenk, Markus R.; Chan, Shiao‐Yng (The Journal of physiology, 2023)
Well-regulated placental palmitic acid (PA) and oleic acid (OA) metabolism is vital for optimal placental function and fetal development, but dysregulation occurs with gestational diabetes (GDM). We hypothesized that such dysregulation might arise from increased maternofetal glucose, leptin or insulin concentrations present in GDM, and that dysregulated PA and OA lipid metabolism could be moderated by myo-inositol, a natural polyol and potential GDM intervention. Placental explants from 21 women were incubated with stable isotope-labelled C-PA or C-OA for 48 h. Explants were treated with glucose (5, 10 mm) or leptin (13 nm) or insulin (150 nm) in combination with myo-inositol (0.3, 30, 60 μm). Forty-seven C-PA lipids and 37 C-OA lipids were measured by liquid chromatography-mass spectrometry (LCMS). Compared with controls (5 mm glucose), glucose (10 mm) increased 19 C-OA lipids and nine C-PA lipids, but decreased C-OA phosphatidylethanolamine 38:5 and C-PA phosphatidylethanolamine 36:4. The effects of leptin and insulin were less prominent than glucose, with leptin increasing C-OA acylcarnitine 18:1, and insulin increasing four C-PA triacylglycerides. Most glucose, leptin and insulin-induced alterations in lipids were attenuated by co-incubation with myo-inositol (30 or 60 μm), with attenuation also occurring in all subgroups stratified by GDM status and fetal sex. However, glucose-induced increases in acylcarnitine were not attenuated by myo-inositol and were even exaggerated in some instances. Myo-inositol therefore appears to generally act as a moderator, suppressing the perturbation of lipid metabolic processes by glucose, leptin and insulin in placenta in vitro. Whether myo-inositol protects the fetus and pregnancy from unfavourable outcomes requires further research. KEY POINTS: Incubation of placental explants with additional glucose, or to a lesser extent insulin or leptin, alters the placental production of C-lipids from C-palmitic acid (PA) and C-oleic acid (OA) in vitro compared with untreated controls from the same placenta. Co-incubation with myo-inositol attenuated most alterations induced by glucose, insulin or leptin in C-lipids, but did not affect alterations in C-acylcarnitines. Alterations induced by glucose and leptin in C-PA triacylglycerides and C-PA phospholipids were influenced by fetal sex and gestational diabetes status, but were all still attenuated by myo-inositol co-incubation. Insulin differently affected C-PA triacylglycerides and C-PA phospholipids depending on fetal sex, with alterations also attenuated by myo-inositol co-incubation.